2004
DOI: 10.1111/j.1461-0248.2004.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of atmospheric CO2 promotes phytoplankton productivity

Abstract: It is usually thought that unlike terrestrial plants, phytoplankton will not show a significant response to an increase of atmospheric CO 2 . Here we suggest that this view may be biased by a neglect of the effects of carbon (C) assimilation on the pH and the dissociation of the C species. We show that under eutrophic conditions, productivity may double as a result of doubling of the atmospheric CO 2 concentration. Although in practice productivity increase will usually be less, we still predict a productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
121
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(139 citation statements)
references
References 29 publications
11
121
4
3
Order By: Relevance
“…Our findings are consistent with previous reports that CO 2 availability can limit phytoplankton productivity in a wide range of conditions, including nutrientreplete freshwater cultures [16] and nutrient-poor oceans [15].…”
Section: (A) Effectiveness Of Co 2 Treatmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous reports that CO 2 availability can limit phytoplankton productivity in a wide range of conditions, including nutrientreplete freshwater cultures [16] and nutrient-poor oceans [15].…”
Section: (A) Effectiveness Of Co 2 Treatmentsupporting
confidence: 93%
“…This assumption is challenged by the presence of inducible carbon concentration mechanisms (CCMs), which increase the local concentration of CO 2 around RuBisCo in the chloroplast when the external concentration is low [14]. Moreover, there is a growing body of evidence that enrichment with CO 2 increases productivity in a diversity of aquatic systems [15][16][17]. We are gaining a growing understanding of the growth response of phytoplankton to CO 2 , including the effect of nutrient availability and the physiological mechanism underlying it [18,19].…”
Section: Introduction (A) the Response Of Primary Producers To Risingmentioning
confidence: 99%
“…The use of an asterisk above the data indicates statistical differences between the two treatments for each phylotype. (4) 412 (15) 53 (5) 81 233 (6) 417 (7) 71 (4) plankton species has been demonstrated to be carbon Zondervan et al 2002;Schippers et al 2004). Similarly, a .…”
Section: Discussionmentioning
confidence: 99%
“…Algal photosynthesis is directly dependent on the concentration of CO 2 at the site of carbon fixation and, as such, it has been suggested that OA could have significant implications for marine primary productivity (Rost et al 2008). For example, the productivity of certain species of marine phytoplankton has been predicted to increase by up to 40% if atmospheric pCO 2 were to double (Schippers et al 2004).…”
mentioning
confidence: 99%
“…Similarly, the evolutionary loss of bicA in several Microcystis strains might be explained by natural selection during periods of low C i availability. Conversely, rising atmospheric CO 2 concentrations may enhance the C i availability in lakes, alleviating cyanobacterial blooms from carbon limitation (Schippers et al, 2004). This would disfavor high-affinity C i uptake systems (Collins et al, 2006), whereas strains with bicA will have a selective advantage in a high-CO 2 world.…”
Section: Growth Under Different C I Conditionsmentioning
confidence: 99%